Immunocytochemical characteristic of the endometrial mucosa HIV-infected women - Irina N. Vorobtsova; Natalya I. Tapilskaya; Elena S. Orlova; Nikolay N. Rukhlyada; Sergei N. Proshin; Ruslan I. Glushakov (IP Berlin A.V., 2020)
Relevance. Human immunodeficiency virus (HIV) infection is an independent factor in reduced fertility and a risk factor for miscarriage. There are some date an endometrial receptivity of HIV-infected patients has changed that plays an important role in embryo invasion, but the true reasons for the decrease in fertility rate in HIV infection remain unknown. Aim. Study of the expression of CD20, CD56 and TLR9 antigens on uterine epithelial cells of HIV-infected patients and the effectiveness of treatment for chronic endometritis by sodium nucleospermate. Materials and methods. This parallel-group study was done at two centres in the Russia. Participants were adults women aged 26 to 49 years (mean age 33.352.9 years), who were HIV-infected (n=12) and HIV-negative (22). An immunocytochemical study of endometrial biopsies taken on the 710th day of the menstrual cycle before and after treatment was done. The course of treatment with sodium nucleospermate was 42 days. Results. The expression level of CD56 and TLR9 in HIV-infected patients was 7.640.92% and 0.330.18%, respectively, and significantly differed from the expression levels in HIV-seronegative patients. There was a decrease in the expression levels of CD20 and CD56 and an increase in the expression levels of TLR9 in all groups of patients after treatment with sodium nucleospermate. Conclusion. A decrease TLR9 expression on uterine epithelial cells in HIV-infected patients showing lack of ability of innate immunity to eliminate pathogens associated with subclinical inflammation and it correlates with an increase in the expression of markers of chronic endometritis.